Antibiotic use and irrational antibiotic prescriptions in 66 primary healthcare institutions in Beijing City, China, 2015-2018 - Yumiti Taxifulati; Haishaerjiang Wushouer; Mengyuan Fu; Yue Zhou; Kexin Du; Xi Zhang; Yaoyao Yang; Bo Zheng; Xiaodong Guan; Luwen Shi (BMC, 2021)
Abstract Objectives To identify the patterns of antibiotic use and irrational antibiotic prescriptions in primary healthcare institutions (PHIs) in Dongcheng District of Beijing, China. Materials and methods All primary healthcare institutions (7 community healthcare centres and 59 community healthcare stations in total) in Dongcheng District were included in the study. Prescription data from January 2015 to December 2018 was derived from the Beijing Prescription Reviewing System of Primary healthcare institutions and analysed retrospectively. The antibiotic prescription rate was calculated and cases of irrational antibiotic prescriptions were identified. Results We extracted 11,166,905 prescriptions from the database. Only 189,962 prescriptions were included in the study, among which 9167 (4.8%) contained antibiotics. The antibiotic prescription rate fell from 5.2% in 2015 to 4.1% in 2018 while irrational antibiotic prescription rate increased from 10.4 to 11.8%. Acute Bronchitis was the most prevalent diagnosis (17.6%) for antibiotic prescriptions, followed by Unspecified Acute Respiratory Tract Infection (14.4%), Acute Tonsillitis (9.9%), and Urinary Tract Infection (6.4%). Around 10% of the prescriptions for the top 7 diagnoses identified were rated as irrational. Cephalosporins, fluoroquinolones, and macrolides were the most prescribed antibiotics, which accounted for 89.3% of all antibiotic prescriptions. Of all the antibiotic prescriptions, 7531 were reviewed, among which 939 (12.5%) were rated as irrational because of antibiotic use. Among all the irrational prescriptions, prescriptions with inappropriate antibiotic use and dosage accounted for the majority (54.4%). Conclusion Although a relatively low level of antibiotic utilization was found in PHIs in Dongcheng District of Beijing, the utilization patterns differed considerably from developed countries and irrational prescriptions remained. Considering the imbalanced allocation of medical resources between primary healthcare setting and secondary and tertiary hospitals, there need to be more efforts invested in regions with different levels of economic development.